2016
DOI: 10.22547/ber/8.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment at Workplace and its Impact on Employee Turnover Intentions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
3
16
0
5
Order By: Relevance
“…We also excluded five studies that did not include a measure of sexual harassment or did not include the prevalence estimate despite a mention in the abstract. [21][22][23][24][25] data screening, extraction and quality appraisal The first author (MR) and last author (HS) initially screened records by title and abstract according to the inclusion and exclusion criteria. Full-text articles were then reviewed by one reviewer (MR) for eligibility and then double-checked by a second reviewer (HS).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…We also excluded five studies that did not include a measure of sexual harassment or did not include the prevalence estimate despite a mention in the abstract. [21][22][23][24][25] data screening, extraction and quality appraisal The first author (MR) and last author (HS) initially screened records by title and abstract according to the inclusion and exclusion criteria. Full-text articles were then reviewed by one reviewer (MR) for eligibility and then double-checked by a second reviewer (HS).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Street harassment is rampant across almost all public places, including educational institutions, workplaces, hospitals, markets, parks, public transport and streets corners (Salman, Abdullah, & Saleem, 2016). Despite all the tangible contributions women have recorded in every field of life in South Asia, it has been systematically engrained in the psyche of the women folk that they cannot stake their claim to equality with men (Banu, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a South Asian context, the euphemistic expression of ‘Eve-teasing’ is also used to denote an array of such acts against women. Though the term is allegedly of Indian origin, the phenomenon is commonly observed and experienced across all countries in South Asia (Salman et al, 2016). The present study puts forth the argument that this practice should not be construed as innocuous street fun but, rather, a grave act targeting women.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Merkin and Shah [ 41 ] found that respondents who experienced sexual harassment had a higher turnover intention and rate of absenteeism compared to the respondents without such an experience. Salman et al [ 42 ] suggested that sexual harassment and turnover intention are closely related. Therefore, the following hypothesis is proposed:…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%